Strategi Promosi Usaha Mikro, Kecil dan Menengah (UMKM) Sale Pisang di Desa Cikatomas Kecamatan Cilograng Kabupaten Lebak - Riny Handayani (P3M FIA UNKRIS, 2024)
This activity, which will be held from January to February 2024, is one of the main programs of the Student Work Lecture (KKM) implemented by Sultan Ageng Tirtayasa University (Untirta). This program, which focuses on developing the potential in the KKM location, namely Cikatomas Village, Cilograng District, Lebak Banten Regency, aims to help introduce the village's potential to the general public. The Central Government through the Ministry of Cooperatives and UKM has launched the OVOP Program or better known as the abbreviation One Village One Product/One Village One Product Approach, while the meaning of OVOP is an approach to developing regional potential in one region to produce one unique global class product according to regional characteristics. by utilizing local resources. The aim of this community service activity is to socialize the development of Micro, Small and Medium Enterprises (MSMEs) which have been operating for quite a long time in Cikatomas Village. The method used is coaching by socializing how to utilize social media in the form of WhatsApp, Facebook and Instagram which are used to promote the village's specialty banana chips UMKM. The result of this activity is to update the packaging of the banana sale products to make them more attractive and increase marketing or promotion of the banana sale business by posting merchandise on forums and buying and selling groups on WhatsApp, Facebook and Instagram.